Entomological studies at the UWM Field Station - (:unkn) unknown (My University, 1977)
Although the invertebrate fauna represents the greatest number of species and individuals within most animal communities, little work on them has been done at the UWM Field Station. Most of the invertebrate work which has been done used insects, which are the largest class of animals. This reflects the orientation of the invertebrate zoologists at UWM towards the Center for Great Lakes Studies and the lack of an entomologist orientated to field work. This report is a statement of where we stand at the Field Station as far as past entomological research is concerned and where we are going in the next year or two.
Keywords: insects; entomology